ABC: An Agent Based Exploration of the Macroeconomic Effects of Covid-19 - Domenico Delli Gatti; Severin Reissl (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We employ a new macro-epidemiological agent based model to evaluate the “lives vs livelihoods” trade-off brought to the fore by Covid-19. The disease spreads across the networks of agents' social and economic contacts and feeds back on the economic dimension of the model through various channels such as employment and consumption demand. We show that under a lockdown scenario the model is able to closely reproduce the epidemiological dynamics of the first wave of the coronavirus epidemic in Lombardy. We then explore the efficacy of the fiscal response to Covid-19 which may take different routes: income support, liquidity provision, credit guarantees. In an agent based setting we gain additional insights on the way in which fiscal measures impact not only on GDP but also on the defaults of firms and the allocation of inputs. We find that liquidity support for firms, a short-time working scheme with compensation for workers, and direct transfer payments to households are effective policy tools to alleviate the economic impact of the epidemic and the lockdown.
Keywords: E21; E22; E24; E27; E62; E65; 330; agent-based models; epidemic; Covid; fiscal policy